Person-organization fit as a mediator of relationship between work environment and stress among social workers - Małgorzata Waszkowska; Aleksandra Andysz; Dorota Merecz (Nofer Institute of Occupational Medicine, 2014)
Background: Occupational stress of social workers is associated with various psychosocial hazards in the work environment. Some of them affect person-organization fit (P-O fit). The aim of the study was to verify a hypothesis on the mediating role of P-O fit in the relationship between work environment and stress. Material and Methods: The research was based on a sample of 500 social workers directly involved in social work. The data were obtained using the Person-Organization Fit Questionnaire by Czarnota-Bojarska, the Work Environment Questionnaire developed by the Department of Occupational Psychology, Nofer Institute of Occupational Medicine, Łódź, and the Perceived Stress Scale (PSS-10) by Cohen et al. Results: As revealed by the regression analysis of the 4 analyzed work environment factors, only organizational politics was significantly related with perceived stress. Complementary and supplementary dimensions of P-O fit and identification with organization were the mediators of the relationship between organizational policies and stress, but only complementary fit proved to be a total mediator. Conclusions: The results of the study suggest that person-organization fit, especially its complementary aspect, is an essential determinant of accomplishing the core functions of social work and good practice among social workers. Med Pr 2014;65(2):219-228